The skin microbiome of infected pressure ulcers: A review and implications for health professionals. (20th October 2021) - Gomes, Fernanda; Furtado, Guilherme Eustáquio; Henriques, Mariana; Sousa, Liliana Baptista; Santos‐Costa, Paulo; Bernardes, Rafael; Apóstolo, João; Parreira, Pedro; Salgueiro‐Oliveira, Anabela
Abstract: Background: Pressure ulcers (PUs) are injuries resulting from ischaemia caused by prolonged compression or shear forces on the skin, adjacent tissues and bones. Advanced stages of PUs are associated with infectious complications and constitute a major clinical challenge, with high social and economic impacts in health care. Goals: This study aims to identify and describe the relationship between PU risk factors, stages and anatomical locations, and the relevance of microbial cohabitation and biofilm growth. Methods: The narrative review method to advocating a critical and objective analysis of the current knowledge on the topic was performed. Indexed databases and direct consultation to specialized and high‐impact journals on the subject were used to extract relevant information, guided by co‐authors. The Medical Subject Headings of pressure ulcer (or injury), biofilms, infection and other analogues terms were used. Results: Development of PUs and consequent infection depends on several direct and indirect risk factors, including cutaneous/PU microbiome, microclimate and behavioural factors. Infected PUs are polymicrobial and characterized by biofilm‐associated infection, phenotypic hypervariability of species and inherent resistance to antimicrobials. The different stages and anatomical locations also play an important role in their colonization. The prevention and monitoring of PUs remain crucial for avoiding the emergence of systemic infections and reducing health care–associated costs, improve the quality of life of patients and reduce the mortality‐associated infected PUs.